An integrated biorefinery approach for bioethanol production from sugarcane tops. (10th June 2022) - Sherpa, Knawang Chhunji; Kundu, Debajyoti; Banerjee, Subhodeep; Ghangrekar, Makarand Madhao; Banerjee, Rintu
Abstract: Bioethanol from lignocellulosic biomass is a promising alternative to petroleum-based fuels to alleviate greenhouse gas emissions and reduce the dependency on fossil fuels. The lignocellulosic biomass is exploited for ethanol production due to its sustainability and abundance. Sugarcane tops, an agricultural residue, was employed in the present investigation to assess its potential as a feedstock for bioethanol production by adopting different fermentation approaches, namely separate fermentation, simultaneous saccharification and fermentation (SSF) and partially consolidated bioprocessing (PCBP). The present study demonstrated the potential of mono and co-fermentation for ethanol production. Comparison between separate fermentation and SSF using S.cerevisiae showed the latter to be more efficient with ethanol production of 5.69% (v/v) in 30.67 h of fermentation time than separate fermentation with 3.76% (v/v) ethanol in 48 h. An integrated fermentation strategy stated as partially consolidated bioprocessing (PCBP) was investigated to improve fermentation efficiency. This process integrates simultaneous pretreatment and saccharification (SPS), conducted by enzyme blends of laccase and cellulase followed by co-fermentation using S. cerevisiae and xylose-fermenting yeast AKBR 212. This approach resulted in a 7.57% (v/v) maximum ethanol concentration in 24.30 h. The different fermentation strategies involved enzymes and yeasts only, thus offering a green biotechnology approach towards converting sugarcane tops into bioethanol. Graphical abstract: Image 1 Highlights: Sugarcane tops was explored for bioethanol production by adopting an eco-friendly, cleaner biological process. An integrated approach of simultaneous pretreatment and saccharification (SPS) followed by co-fermentation was adopted. The maximum ethanol yield obtained was 7.57% (v/v) in 24.3 h under partially consolidated bioprocessing (PCBP).